THE IMPLEMENTATION OF MEDIA IN ENGLISH LANGUAGE TEACHING - Regina Rahmi (Jurnal Visipena, 2014)
This study which was conducted at SD Islam Laboratorium Neuhen, Mesjid Raya is intended to figure out how the implementation of media in English language teaching to the six levels. The study was conducted case study research design. The population was 44 and the sample was taken by using nonprobability sample that is convenience sampling was 22 students and 1 English teacher. The research problems are: (1) what kinds of media are used by the teacher in teaching English? (2) how does the teacher implement media in teaching English? (3) what are the obstacles faced by the teacher in teaching English by using media (4) what are students’ responses toward using media in English language teaching? The data were collected by using instruments, namely: observation checklist sheets, questionnaire sheet, interview guidelines, and documentations.Based on the data analysis, it was found that (1) the English teacher at SD Islam Laboratorium used (a) smart phone as audio media (b) visual printed media such as book, magazine and newspaper (c) visual display media such as picture, flashcard, poster, realia/model/mock up, puzzle and blackboard (d) teacher herself as model (2) the teacher did three phases in using media. They are: (a) preparation; learning curriculum and syllabus, the teacher matches the basic competences with appropriate media, preparing the media, bring the media to the class, recognizing the types of the students (b) core activity; students’ question about media, student-centered in learning process while using media, good interaction in using media, cognitive-affective-psychomotor of the student in using media (c) closing; summarization of using media, motivation/moral value of using media, giving homework. In addition the teacher did positive performance in using media (3) some difficulties faced by the teacher in the implementation of media in English language teaching, they are: designing lesson plan and preparing appropriate teaching materials as media (4) the students' responses toward the implementation of media was very positive. The findings show that 90% of the students like to study English by using media. So, it is suggested that English teacher should use the media, because they are the effective tools in English teaching-learning process.